Paediatric neurology (Churchill Livingstone, 1997)
The book offers a clear recognition of the numerous epilepsy syndromes of childhood, many of them with genetic implications, has increased our diagnostic abilities and allowed more rational decisions on investigation, prognosis and treatment. This book is written by six authors in their areas of special expertise